Directions of Research the Development of the Tourism and Recreational Sphere as an Object of State Administration - Boretska, N.; Krapivina, G. (Економічний вісник Донбасу, 2022)
The article is devoted to the possibilities of applying the cluster approach based on public-private partnership in the development of tourist and recreational areas during the period of restoration of the economic development of Ukraine. Although this approach has become widespread, today it requires a deep rethinking and justification of effective ways to apply it at all levels of government, taking into account the interests of business and the state in the special conditions that have developed in Ukraine. The article substantiates the resource prerequisites and the feasibility of creating a tourist and recreational cluster, its composition and characteristic features. The modern problems of formation and development of tourist and recreational clusters on the basis of public-private partnership are revealed and its structure is proposed, which includes three segments: a core consisting of tour operators and travel agents; the basis of the cluster, that is, enterprises serving tourists and recreants, related enterprises serving the cluster; cluster infrastructure. It is proved that in order to determine the optimal structure of the cluster, not only in terms of its components, but taking into account the spatial approach, it is necessary to study the tourist and recreational market of territories. No less important for justifying the development of tourist and recreational areas is the study of the free time of the population and the possibilities of the labor market to meet the needs of business structures.